Magnetic carrier and two-component developer
Patent Information
- Application Number
- JP2022205170
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-12-22
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2042-12-22
AI Technical Summary
【0007】 本発明によれば、高湿環境から低湿環境へ環境が変動した後においても即座に環境になじみ、安定した画像濃度を出力できる磁性キャリアを提供することができる。 また本発明によれば、低湿環境で且つ低トナー消費の状態で使用された直後でも、安定した画像濃度を出力できる磁性キャリアを提供することができる。
Smart Images

Figure 0007638948000015 
Figure 0007638948000016 
Figure 0007638948000017
Abstract
Description
[Technical field]
[0001] The present invention relates to a magnetic carrier and a two-component developer used in an image forming method for visualizing an electrostatic image by electrophotography. [Background technology]
[0002] Conventionally, in the electrophotographic image forming method, a method is generally used in which an electrostatic latent image is formed on an electrostatic latent image carrier by using various means, and toner is attached to the electrostatic latent image to develop it. In this development, a two-component development method is widely adopted in which carrier particles called magnetic carrier are mixed with the toner, and the toner is triboelectrically charged to give an appropriate amount of positive or negative charge to the toner, and the charge is used as a driving force for development. In the two-component development method, functions such as stirring, transporting, and charging the developer can be imparted to the magnetic carrier, so the division of functions between the magnetic carrier and the toner is clear, and this has the advantage of good controllability of developer performance. Here, the magnetic carrier often has a core that is magnetized to obtain transportability, and a resin coating that provides the ability to impart charge to the toner. In recent years, the demand for electrophotography has been constantly increasing, and various added values are being sought, one of which is high stability. Stability includes long-term stability, i.e., image quality does not deteriorate even with long-term use, and environmental stability, i.e., image quality does not change even when the environment changes. Among these, there are examples in which a carrier is coated with a resin that uses an amino group, or the core is treated with an amino group primer, for the purpose of maintaining charge stability for a long period of time or improving charge imparting properties in a high humidity environment (Patent Documents 1 to 9). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent No. 6882644 [Patent Document 2] JP 2021-131481 A [Patent Document 3] JP 2014-178704 A [Patent Document 4] Patent No. 4966880 [Patent Document 5] Patent No. 5079563 [Patent Document 6] JP 2006-330307 A [Patent Document 7] Patent No. 6403816 [Patent Document 8] Patent No. 6584225 [Patent Document 9] Patent No. 4505687 Summary of the Invention [Problem to be solved by the invention]
[0004] Although the above-mentioned conventional techniques have been effective in improving the charging stability, among the various demands in recent years, there is a demand for the copying machine body and developer to be able to quickly adapt to the environment even when the environment changes from a high humidity environment to a low humidity environment, and to output a stable image density. It has been found that there is still room for improvement in meeting such demands. In view of the above, the present invention has an object to solve the above problems, specifically, to provide a magnetic carrier capable of outputting a stable image density even when the environment changes from a high humidity environment to a low humidity environment by containing fine particles that have been surface-treated with a compound having a hydrophobic component and an amino group in a coating. [Means for solving the problem]
[0005] The present invention provides a magnetic carrier having a magnetic core particle and a resin coating layer that coats the surface of the magnetic core particle, The resin coating layer contains fine particles, The fine particles relate to a magnetic carrier having a fine particle matrix and a structure represented by the following formula (1) present on the surface of the fine particle matrix. *-X1 -A formula (1) [X 1 satisfies either (i) or (ii) of the following provisions: (i)-(SiR a R b -O)n-, R a and R b is CH3 or C6H5, R a and R b may be the same or different, and n is an integer of 3 to 20. (ii) -(CH2-CR c R d )m-, R c and R d is either H, CH3, C2H5 or C3H7, and R c and R d may be the same or different, and m is an integer of 2 or more and 10 or less; A is, X 1 When the compound has the structure of (i), it is a structure represented by the following formula (2-1) or the following formula (2-2): X 1 When the compound has the structure (ii), the compound is any structure selected from the group consisting of the following formulas (2-3) to (2-5): * indicates the bonding portion with the microparticle matrix.
[0006] [ka] (R in the above formulas (2-1) to (2-5) e and R f is either H, CH3, C2H5, C3H7, C4H9, C6H5, CH2OH, C2H4OH or CH2O-CH3, and Re and Rf may be the same or different. R g and R h is either CH3, O-CH3 or O-C2H5, and R g and R h may be the same or different. R i is H or CH3. p, q, and r each represent an integer between 1 and 10. s and t each represent an integer between 1 and 10. u, v, and w represent integers between 1 and 10.)] The present invention also relates to a two-component developer having the above magnetic carrier and a toner. Effect of the Invention
[0007] According to the present invention, it is possible to provide a magnetic carrier that can quickly adapt to an environment even after the environment changes from a high humidity environment to a low humidity environment, and can output a stable image density. Furthermore, according to the present invention, it is possible to provide a magnetic carrier that can output a stable image density even immediately after use in a low humidity environment and under conditions of low toner consumption. [Brief description of the drawings]
[0008] [Figure 1] FIG. 1 is a schematic diagram of an image forming apparatus suitable for forming an image using the present invention. [Diagram 2] FIG. 1 is a schematic diagram of an image forming apparatus suitable for forming a full-color image using the present invention. [Diagram 3] FIG. 2 is a schematic diagram of a surface treatment device suitable for surface treatment of the toner for the developer of the present invention. [Figure 4] FIG. 2 is a schematic diagram of a resistivity measuring device used in the magnetic carrier core of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] In the present invention, the expressions "xx or more and xx or less" and "xx to xx" expressing a numerical range mean a numerical range including the lower and upper limit endpoints, unless otherwise specified.
[0010] [Features of the present invention] The magnetic carrier of the present invention is a magnetic carrier having a magnetic core particle and a resin coating layer that coats the surface of the magnetic core particle, The resin coating layer contains fine particles, The fine particles include a fine particle matrix and a compound represented by the following formula (1) present on the surface of the fine particle matrix: *-X 1 -A formula (1) It has a structure represented by the following formula:
[0011] That is, although the details of formula (1) will be described later, the carrier of the present invention has a hydrophobic component (X in formula (1)) on the substrate side (the side where a bond with the microparticle matrix is formed). 1 The magnetic carrier has a characteristic that the magnetic carrier contains, in a coat (resin coating layer), fine particles that have been surface-treated with a compound having the structure (A in formula (1)) and an amino group at the terminal.
[0012] Conventionally, it is well known that charge adjustment is performed by using amino groups in the resin coating layer. One method of adjusting charge is to incorporate amino groups into the coating resin component itself. This improves the charge imparting performance of the carrier, but it also increases the charge imparting performance in low humidity environments, which raises concerns about differences in image density between low humidity and high humidity environments.
[0013] It is also known that the surface layer of the magnetic carrier core is primer-treated with a component having an amino group, and then coated with a resin for coating to adjust the charge. Although this method does not provide a high charge-imparting property, it is possible to reduce the difference in image density between low and high humidity environments by improving the charge in a high humidity environment.
[0014] However, when charge adjustment is performed using these methods, it was found that there was an issue in which the image density became unstable when the humidity environment changed from high to low. It was believed that this was due to the influence of hydrophilic amino groups, which made it difficult for the moisture attracted in a high humidity environment to be released when the humidity environment changed to low.
[0015] Therefore, the present inventors have considered whether it is possible to improve the releasability of moisture attracted in a high humidity environment by arranging a hydrophobic component near the amino group. As a result of intensive investigation into the composition, they have devised a method of surface-treating the fine particles so that the part of the fine particles that reacts with the base material has a hydrophobic component, and the fine particles have a structure with amino groups on the surface side of the fine particles, and then containing the fine particles in the coating resin. As a result, it has been possible to improve the stability of image density when changing from a high humidity environment to a low humidity environment compared to conventional magnetic carriers containing amino groups.
[0016] [Each configuration of the present invention] <Fine particles added to carrier> The fine particles added to the magnetic carrier of the present invention have a fine particle matrix and a structure represented by the following formula (1) present on the surface of the fine particle matrix. *-X 1 -A formula (1) [X 1 satisfies either (i) or (ii) of the following provisions: (i)-(SiR a R b -O)n-, R a and R b is CH3 or C6H5, R a and R b may be the same or different, and n is an integer of 3 to 20. (ii) -(CH2-CR c R d )m-, R c and R d is either H, CH3, C2H5 or C3H7, and R c and R d may be the same or different, and m is an integer of 2 or more and 10 or less; A is, X 1 When the compound has the structure of (i), it is a structure represented by the following formula (2-1) or the following formula (2-2): X 1 When the compound has the structure (ii), the compound is any structure selected from the group consisting of the following formulas (2-3) to (2-5): * indicates the bonding portion with the microparticle matrix.
[0017] [ka] (R in the above formulas (2-1) to (2-5) e and R f is H, CH3, C2H5, C3H7, C4H9, C6H5, CH2OH, C2H4OH or CH2O-CH3, and R e and R f may be the same or different. R g and R h is either CH3, O-CH3 or O-C2H5, and R g and R h may be the same or different. R i is H or CH3. p, q, and r each represent an integer between 1 and 10. s and t each represent an integer between 1 and 10. u, v, and w represent integers between 1 and 10.)]
[0018] Here, for example, X 1 has the structure of the above (i), and if A is the above formula (2-1), then it has the following formula (3-1); 1 has the above structure (i) and A is the above formula (2-2), the formula is as shown in the following formula (3-2).
[0019] [ka]
[0020] In the above configuration, X 1 When the toner has the structure (i), n is 3 or more and 20 or less, or when the toner has the structure (ii), m is 2 or more and 10 or less, thereby improving the stability of image density when the toner changes from a high-humidity environment to a low-humidity environment. n is preferably 4 or more and 16 or less, and m is preferably 4 or more and 6 or less.
[0021] The amount of the compound having the above structure to be treated with respect to the base particles is preferably 2.0 parts by mass or more and 50.0 parts by mass or less per 100.0 parts by mass of the base particles. By setting the amount to be treated in this range, the surface treatment of the base particles can be stably performed.
[0022] The base particles, which are the base material of the fine particles, may be fine particles of either organic or inorganic materials, but crosslinked resin fine particles or inorganic fine particles that have the strength to maintain the shape of the fine particles when coated are preferred. Examples of crosslinked resins that form crosslinked resin fine particles include crosslinked polymethyl methacrylate resin (PMMA resin), crosslinked polystyrene resin, melamine resin, guanamine resin, urea resin, phenolic resin, and nylon resin. Examples of inorganic fine particles include silica, alumina, titania, etc.
[0023] Furthermore, the number-average particle diameter of the primary particles of the fine particles is preferably 8 nm or more and 100 nm or less, which further improves the stability of the image density when the humidity environment is changed from a high humidity environment to a low humidity environment.The number-average particle diameter of the primary particles is more preferably 10 nm or more and 80 nm or less.
[0024] The content of the fine particles used in the present invention is preferably 1.0 to 100.0 parts by mass relative to 100 parts by mass of the coating resin, more preferably 10.0 to 80.0 parts by mass. By keeping the content within the above range, the stability of the image density when changing from a high humidity environment to a low humidity environment is further improved, and the stability of the density immediately after use in a low humidity environment with low toner consumption is also improved.
[0025] <Carrier coating resin> As the coating resin used in the present invention, known resins can be used.
[0026] Examples of thermoplastic resins include acrylic resins such as polymethyl methacrylate and cyclohexyl methacrylate-methyl methacrylate copolymers, polystyrene, styrene-acrylic acid ester copolymers, styrene-methacrylic acid ester copolymers, styrene-butadiene copolymers, ethylene-vinyl acetate copolymers, polyvinyl chloride, polyvinyl acetate, polyvinylidene fluoride resins, fluorocarbon resins, perfluorocarbon resins, solvent-soluble perfluorocarbon resins, polyvinylpyrrolidone, petroleum resins, novolac resins, saturated alkyl polyester resins, aromatic polyester resins such as polyethylene terephthalate, polybutylene terephthalate, and polyarylate, polyamide resins, polyacetal resins, polycarbonate resins, polyethersulfone resins, polysulfone resins, polyphenylene sulfide resins, and polyether ketone resins.
[0027] Examples of thermosetting resins include phenolic resins, modified phenolic resins, maleic resins, alkyd resins, epoxy resins, acrylic resins, unsaturated polyesters obtained by polycondensation of maleic anhydride, terephthalic acid, and polyhydric alcohols, urea resins, melamine resins, urea-melamine resins, xylene resins, toluene resins, guanamine resins, melamine-guanamine resins, acetoguanamine resins, glyptal resins, furan resins, silicone resins, polyimides, polyamideimide resins, polyetherimide resins, and polyurethane resins.
[0028] Among these, acrylic resins, polyester resins, epoxy resins, and urethane resins are preferred.
[0029] <Other additives> The coating resin layer of the present invention may contain conductive fine particles in the coating resin. The conductive fine particles can appropriately control the resistivity of the electrophotographic carrier. The content of the conductive fine particles added to the coating resin is preferably 0.1 parts by mass or more and 20 parts by mass or less with respect to 100 parts by mass of the coating resin. Examples of the conductive fine particles include carbon black, titanium oxide, and silver.
[0030] <Carrier core and its manufacturing method> For the magnetic carrier core of the present invention, known magnetic particles such as magnetite particles, ferrite particles, magnetic material-dispersed resin particles, etc. can be used. Among them, magnetic particles obtained by filling the pores of porous magnetic particles with a resin or magnetic material-dispersed resin particles, i.e., magnetic particles containing a magnetic oxide and a resin composition, are preferred from the viewpoint of extending the life since they can reduce the specific gravity of the magnetic carrier.
[0031] Reducing the specific gravity of the magnetic carrier reduces the load on the toner in the developer state in the developing device, prevents the adhesion of toner components to the magnetic carrier surface, reduces the load on the carriers themselves, and further suppresses peeling, chipping, and scraping of the coating resin layer. It also improves dot reproducibility, making it possible to obtain high-definition images.
[0032] In addition, the resin contained in the pores of the porous magnetic particles can be a copolymer resin used as a coating resin, but is not limited to this and can be any known resin. As the thermoplastic resin, the copolymer used as the coating resin is preferable, but other examples include the following. Polystyrene, polymethyl methacrylate, styrene-acrylic acid ester copolymer, styrene-methacrylic acid ester copolymer, styrene-butadiene copolymer, ethylene-vinyl acetate copolymer, polyvinyl chloride, polyvinyl acetate, polyvinylidene fluoride resin, fluorocarbon resin, perfluorocarbon resin, solvent-soluble perfluorocarbon resin, polyvinylpyrrolidone, petroleum resin, novolac resin, saturated alkyl polyester resin, polyethylene terephthalate, polybutylene terephthalate, aromatic polyester resin such as polyarylate, polyamide resin, polyacetal resin, polycarbonate resin, polyethersulfone resin, polysulfone resin, polyphenylene sulfide resin, polyether ketone resin.
[0033] Examples of thermosetting resins include the following: phenol resins, modified phenol resins, maleic resins, alkyd resins, epoxy resins, acrylic resins, unsaturated polyesters obtained by polycondensation of maleic anhydride, terephthalic acid, and polyhydric alcohols, urea resins, melamine resins, urea-melamine resins, xylene resins, toluene resins, guanamine resins, melamine-guanamine resins, acetoguanamine resins, glyptal resins, furan resins, silicone resins, polyimides, polyamideimide resins, polyetherimide resins, and polyurethane resins.
[0034] As a method for filling the voids of the ferrite particles having a porous shape with a resin component, there is a method of diluting the resin component in a solvent and adding the diluted solution to the porous magnetic core particles. The solvent used here may be any solvent capable of dissolving each resin component. In the case of a resin soluble in an organic solvent, an organic solvent such as toluene, xylene, cellosolve butyl acetate, methyl ethyl ketone, methyl isobutyl ketone, or methanol may be used. In the case of a water-soluble resin component or an emulsion-type resin component, water may be used. As a method for adding a resin component diluted with a solvent to the inside of the porous magnetic core particles, there is a method of impregnating the resin component by a coating method such as a dipping method, a spraying method, a brush coating method, a fluidized bed method, or a kneading method, and then volatilizing the solvent. In the case of filling with a thermosetting resin, after volatilizing the solvent, the temperature is raised to the temperature at which the resin used hardens, and a hardening reaction is carried out.
[0035] On the other hand, specific methods for producing magnetic material-dispersed resin particles include the following. For example, submicron magnetic materials such as iron powder, magnetite particles, and ferrite particles are kneaded so as to disperse them in a thermoplastic resin, pulverized to a desired carrier particle size, and, if necessary, subjected to a thermal or mechanical spheroidizing treatment to obtain the particles. It is also possible to produce the magnetic material-dispersed resin particles by dispersing the magnetic material in a monomer and polymerizing the monomer to form a resin.
[0036] In this case, the resin may be a vinyl resin, a polyester resin, an epoxy resin, a phenol resin, a urea resin, a polyurethane resin, a polyimide resin, a cellulose resin, a silicone resin, an acrylic resin, or a polyether resin. The resin may be one type or a mixture of two or more types. In particular, a phenol resin is preferable in terms of increasing the strength of the carrier core. The true density and resistivity can be adjusted by adjusting the amount of the magnetic material. Specifically, in the case of magnetic particles, it is preferable to add 70% by mass or more and 95% by mass or less to the carrier.
[0037] The carrier core preferably has a volume average particle size (D50) of 20 μm to 80 μm in order to enable uniform coating with the coating resin, prevent carrier adhesion, and ensure an appropriate density of the developer magnetic brush to obtain high quality images.
[0038] The resistivity of the carrier core is 1.0×10 at an electric field strength of 1000 (V / cm). 5 (Ω cm) or more 1.0×10 14 (Ω·cm) or less is preferable because good developability can be obtained.
[0039] <Method of coating with resin> The method of coating the carrier core surface with the coating resin is not particularly limited, and can be performed by a known method. For example, there is a so-called immersion method in which the carrier core and the coating resin solution are stirred while volatilizing the solvent, and the carrier core surface is coated with the coating resin. Specific examples include a universal mixer (manufactured by Fuji Paudal Co., Ltd.), a Nauta Mixer (manufactured by Hosokawa Micron Co., Ltd.), and a vacuum degassing kneader. There is also a method in which the coating resin solution is sprayed from a spray nozzle while forming a fluidized bed, and the carrier core surface is coated with the coating resin. Specific examples include a Spiracoater (manufactured by Okada Seiko Co., Ltd.) and a Spiraflow (manufactured by Freund Corporation). There is also a method in which the coating resin is applied to the magnetic carrier core in a particle state in a dry manner. Specific examples include a treatment method using an apparatus such as a Hybridizer (manufactured by Nara Machinery Co., Ltd.), a Mechanofusion (manufactured by Hosokawa Micron Co., Ltd.), a HighFlex Gral (manufactured by Fukae Powtec Co., Ltd.), and a Theta Composer (manufactured by Tokuju Kogyo Co., Ltd.).
[0040] <Magnetic carrier> Next, the magnetic carrier of the present invention will be described.
[0041] The magnetic carrier of the present invention has the above-mentioned fine particles encapsulated inside the coating resin. In this case, the ratio of the N element on the magnetic carrier surface is preferably 0.7 atom % or less. This value is the N element derived from the surface treatment of the above-mentioned fine particles, and by making it 0.7 atom % or less, the stability of the image density when changed to a low humidity environment is further improved, and the density stability immediately after use in a low humidity environment with low toner consumption is also improved. The ratio of the N element on the magnetic carrier surface is more preferably 0.2 atom % or more and 0.5 atom % or less. The ratio of the N element on the magnetic carrier surface can be adjusted by the amount of surface treatment on the fine particles, the type of treatment agent, and the amount of fine particles added.
[0042] In addition, when the average film thickness of the resin coating layer is 100 nm or more and 1000 nm or less, it is effective in terms of concentration stability immediately after use in a low-humidity environment and under low toner consumption conditions, and reduction of the image density difference between wet and high-humidity environments. More preferably, the average film thickness of the resin coating layer is 200 nm or more and 800 nm or less. The average film thickness of the resin coating layer can be controlled by adjusting the total amount of the coating component containing the coating resin and the fine particles.
[0043] From the viewpoint of improving the effects of the present invention, it is preferable that the 50% particle size (D50) based on volume of the magnetic carrier is 20 μm or more and 80 μm or less. More preferably, it is 30 μm or more and 60 μm or less.
[0044] 〔Measurement methods for various physical properties of the carrier〕 Next, the measurement methods for various physical properties of the carrier will be described.
[0045] <Measurement method for the ratio of N element derived from the surface treatment of fine particles by XPS> As a measurement sample, an indium foil is pasted on an XPS dedicated platen, and the magnetic carrier is attached thereon. At this time, the particles are uniformly attached so that the indium foil part is not exposed. The X-ray irradiation location is set to the carrier on the indium foil by the following XPS apparatus. Apparatus used: PHI5000VersaProbeII manufactured by ULVAC-PHI, Inc. Irradiation ray: Al-Kα ray Output: 100 μ25W15kV Photoelectron capture angle: 45° PassEnergy: 58.70 eV Stepsize: 0.125 eV XPS peaks: C2p, O2p, Si2p, N1s, Fe2p, Mn2p Measurement range: 300 μm × 200 μm Measurement is performed under the above conditions, the N element number ratio (atom%) is calculated from the peaks of each element, the measurement location is changed, and the average value when measuring 10 times in total is used as the measurement value.
[0046] <Measurement method for the average film thickness of the resin coating layer> The thickness of the resin coating layer was measured by observing the cross section of the magnetic carrier with a transmission electron microscope (TEM) (50,000x magnification).
[0047] Specifically, the magnetic carrier was subjected to ion milling using an argon ion milling device (Hitachi High-Technologies Corporation, product name E-3500), and the thickness of the resin coating layer on the cross section of the magnetic carrier was measured at any ten points using a transmission electron microscope (TEM) (50,000x magnification each).
[0048] The same measurement as above was carried out for 10 magnetic carriers, and the average of the 20 measured values of the thickness of the resin coating layer obtained was taken as the average thickness (nm) of the resin coating layer. The ion milling measurement conditions were as follows: Beam diameter: 400μm (half width) Ion gun acceleration voltage: 5kV Ion gun discharge voltage: 4kV Ion gun discharge current: 463μA Ion gun irradiation current: 90μA / cm 3 / 1min
[0049] <Method for measuring 50% particle size (D50) based on volume of magnetic carrier> The particle size distribution was measured using a laser diffraction / scattering particle size distribution measuring device "Microtrac MT3300EX" (manufactured by Nikkiso Co., Ltd.).
[0050] The 50% particle size (D50) based on volume of the magnetic carrier was measured using a sample supply device for dry measurement, the "One-Shot Dry Sample Conditioner Turbotrac" (manufactured by Nikkiso Co., Ltd.). The supply conditions for the Turbotrac were a dust collector used as the vacuum source, with an air volume of approximately 33 l / sec and a pressure of approximately 17 kPa. Control was performed automatically on the software. The particle size was calculated as the 50% particle size (D50), which is a cumulative value based on a volume standard. Control and analysis were performed using the attached software (version 10.3.3-202D). The measurement conditions were as follows: SetZero time: 10 seconds Measurement time: 10 seconds Number of measurements: 1 Particle refractive index: 1.81% Particle shape: non-spherical Measurement upper limit: 1408μm Measurement lower limit: 0.243μm Measurement environment: 23℃, 50% RH
[0051] <Measurement of specific resistance of magnetic carrier> The resistivity value of the magnetic carrier is measured using the measuring device shown in FIG.
[0052] The resistivity is measured by filling the cell E with carrier, arranging a lower electrode and an upper electrode so as to be in contact with the carrier particles, applying a voltage between these electrodes, and measuring the current that flows at that time to obtain the resistivity. The measurement conditions for the resistivity in the present invention are: contact area S between the filled carrier and the electrodes = approximately 2.4 cm 2 The sample thickness d = approximately 0.2 cm, and the load on the upper electrode is 240 g (2.35 N). Voltage is applied in the following order under conditions (I), (II), and (III), and the current at the applied voltage under condition (III) is measured. The sample thickness d is then accurately measured, and the resistivity (Ω·cm) at each electric field strength (V / cm) is calculated, and the resistivity at an electric field strength of 3000 V / cm is taken as the resistivity of the sample's magnetic carrier. Application conditions (I): (Change from 0V to 1000V: Increase in steps of 200V every 30 seconds) (II): (1000V hold for 30 seconds) (III): (Change from 1000V to 0V: Decrease in steps of 200V every 30 seconds) · Magnetic carrier resistivity (Ω·cm) = (applied voltage (V) / measured current (A)) × S (cm 2 ) / d(cm) Electric field strength (V / cm) = applied voltage (V) / d (cm)
[0053] The resistivity of magnetite fine particles used in the magnetic material dispersion type resin carrier was also measured in the same manner.
[0054] <Method of measuring the magnetization strength of the carrier core> The magnetization strength of the carrier core can be measured by a vibrating sample magnetometer or a direct current magnetization characteristic recorder (BH tracer). In the examples described later, the magnetization strength is measured by a vibrating sample magnetometer BHV-30 (manufactured by Riken Denshi Co., Ltd.) according to the following procedure.
[0055] A cylindrical plastic container is filled with carrier cores sufficiently densely to prepare a sample. The actual mass of the sample filled in the container is measured. Then, the sample is adhered in the plastic container with instant adhesive so that the sample does not move.
[0056] Using a standard sample, the external magnetic field axis and the magnetization moment axis are calibrated at 5000 / 4π (kA / m).
[0057] The magnetization intensity was measured from the loop of the magnetization moment when an external magnetic field of 5000 / 4π (kA / m) was applied at a sweep speed of 5 (min / roop). From this, the magnetization intensity of the carrier core (Am 2 / kg).
[0058] <Measurement of true specific gravity of magnetic carrier core> The true specific gravity of the magnetic carrier particles can be determined by a dry automatic density meter, an autopycnometer.
[0059] <Quantitative Determination of Coating Amount of Carrier Coating Resin> The measurement equipment used is the AQF-100 automatic sample combustion device (manufactured by Mitsubishi Chemical) and the ICS-2000 ion chromatograph (manufactured by Dionex). The measurement principle is to burn the sample in the automatic sample combustion device, and to use hydrogen peroxide (H2O2) as an absorption liquid to extract the fluorine element in the fluororesin. - and PO4 3- is used as an internal standard substance, and quantitative determination is performed by ion chromatography.
[0060] The measurement conditions for the automatic sample combustion apparatus AQF-100 (manufactured by Mitsubishi Chemical Corporation) are as follows. InletTemp.; 900℃ OutletTemp.;1000℃ Ar / O2; 200ml / min O2: 400ml / min 1st position; 150mm / 60s End Time;360s CoolTime;30s BoatSpeed: 10mm / s
[0061] The measurement conditions for the ion chromatograph ICS-2000 (Dionex Corporation) were as follows: It is. Separation column: AG12A / AS12A Injection volume: 25μl Eluent: 1mM → 40mM (20min) Gradient using an eluent generator The dissolution method is used. Flow rate;1.0ml / min Column oven: 35℃
[0062] <Measurement of the number-average particle size of primary particles> The number-average particle size of the primary particles of the microparticles is measured using a transmission electron microscope "JEM-2800" (JEOL Ltd.). The magnetic carrier particles to which the microparticles have been added are observed at a magnification of up to 200,000 times, and 200 microparticle components are randomly selected to measure the diameter of their major axis and obtain the number-average particle size. The observation magnification is adjusted appropriately depending on the size of the microparticles.
[0063] 〔toner〕 Next, the constitution of the toner which is used together with the carrier as a two-component developer or a replenishing developer in the present invention and which is preferable for achieving the purpose will be described in detail below.
[0064] <Binding resin> The toner particles in the present invention may use the following polymers as the binder resin. Homopolymers of styrene and its substitutes, such as polystyrene, poly-p-chlorostyrene, and polyvinyltoluene; styrene-based copolymers, such as styrene-p-chlorostyrene copolymer, styrene-vinyltoluene copolymer, styrene-vinylnaphthalene copolymer, styrene-acrylic acid ester copolymer, and styrene-methacrylic acid ester copolymer; styrene-based copolymer resin, polyester resin, a mixture of polyester resin and vinyl resin, or a hybrid resin in which both are partially reacted; polyvinyl chloride, phenol resin, naturally modified phenol resin, naturally modified maleic acid resin, acrylic resin, methacrylic resin, polyvinyl acetate, silicone resin, polyester resin, polyurethane, polyamide resin, furan resin, epoxy resin, xylene resin, polyethylene resin, and polypropylene resin. Among these, polyester resin is preferably used as the main component from the viewpoint of low-temperature fixability.
[0065] As the monomers used in the polyester unit of the polyester resin, polyhydric alcohols (divalent or trivalent or higher alcohols), polyvalent carboxylic acids (divalent or trivalent or higher carboxylic acids), their acid anhydrides or their lower alkyl esters are used. Here, in order to create a branched polymer in order to express "strain hardening", it is effective to partially crosslink the amorphous resin molecule, and for this purpose, it is preferable to use a polyfunctional compound having a valence of three or more. Therefore, it is preferable to include a trivalent or higher carboxylic acid, its acid anhydride or its lower alkyl ester, and / or a trivalent or higher alcohol as the raw material monomer of the polyester unit.
[0066] As the polyhydric alcohol monomer used in the polyester unit of the polyester resin, the following polyhydric alcohol monomers can be used.
[0067] Examples of the dihydric alcohol component include ethylene glycol, propylene glycol, 1,3-butanediol, 1,4-butanediol, 2,3-butanediol, diethylene glycol, triethylene glycol, 1,5-pentanediol, 1,6-hexanediol, neopentyl glycol, 2-ethyl-1,3-hexanediol, hydrogenated bisphenol A, and bisphenol represented by formula (A) and its derivatives;
[0068] [ka] (In the formula, R is an ethylene or propylene group, x and y are each an integer of 0 or more, and the average value of x+y is 0 or more and 10 or less.) Diols represented by formula (B);
[0069] [ka]
[0070] Examples of trihydric or higher alcohol components include sorbitol, 1,2,3,6-hexanetetrol, 1,4-sorbitan, pentaerythritol, dipentaerythritol, tripentaerythritol, 1,2,4-butanetriol, 1,2,5-pentanetriol, glycerol, 2-methylpropanetriol, 2-methyl-1,2,4-butanetriol, trimethylolethane, trimethylolpropane, and 1,3,5-trihydroxymethylbenzene. Among these, glycerol, trimethylolpropane, and pentaerythritol are preferably used. These dihydric alcohols and trihydric or higher alcohols can be used alone or in combination.
[0071] As the polybasic carboxylic acid monomer used in the polyester unit of the polyester resin, the following polybasic carboxylic acid monomers can be used.
[0072] Examples of divalent carboxylic acid components include maleic acid, fumaric acid, citraconic acid, itaconic acid, glutaconic acid, phthalic acid, isophthalic acid, terephthalic acid, succinic acid, adipic acid, sebacic acid, azelaic acid, malonic acid, n-dodecenylsuccinic acid, isododecenylsuccinic acid, n-dodecylsuccinic acid, isododecylsuccinic acid, n-octenylsuccinic acid, n-octylsuccinic acid, isooctylsuccinic acid, isooctylsuccinic acid, anhydrides of these acids, and lower alkyl esters thereof. Of these, maleic acid, fumaric acid, terephthalic acid, and n-dodecenylsuccinic acid are preferably used.
[0073] Examples of trivalent or higher carboxylic acids, their anhydrides or their lower alkyl esters include 1,2,4-benzenetricarboxylic acid, 2,5,7-naphthalenetricarboxylic acid, 1,2,4-naphthalenetricarboxylic acid, 1,2,4-butanetricarboxylic acid, 1,2,5-hexanetricarboxylic acid, 1,3-dicarboxyl-2-methyl-2-methylenecarboxypropane, 1,2,4-cyclohexanetricarboxylic acid, tetra(methylenecarboxyl)methane, 1,2,7,8-octanetetracarboxylic acid, pyromellitic acid, empol trimer acid, their anhydrides or their lower alkyl esters. Among these, 1,2,4-benzenetricarboxylic acid, i.e., trimellitic acid or its derivatives, is particularly preferred because it is inexpensive and easy to control the reaction. These divalent carboxylic acids and trivalent or higher carboxylic acids can be used alone or in combination.
[0074] The method for producing the polyester unit of the present invention is not particularly limited, and a known method can be used. For example, the above-mentioned alcohol monomer and carboxylic acid monomer are simultaneously charged, and polymerized through an esterification reaction or an ester exchange reaction and a condensation reaction to produce a polyester resin. The polymerization temperature is not particularly limited, but is preferably in the range of 180°C to 290°C. For the polymerization of the polyester unit, for example, a polymerization catalyst such as a titanium-based catalyst, a tin-based catalyst, zinc acetate, antimony trioxide, or germanium dioxide can be used. In particular, the binder resin of the present invention is more preferably a polyester unit polymerized using a tin-based catalyst.
[0075] In addition, it is preferable from the viewpoint of suppressing fogging that the acid value of the polyester resin is 5 mgKOH / g or more and 20 mgKOH / g or less, and the hydroxyl value is 20 mgKOH / g or more and 70 mgKOH / g or less, since this can suppress the amount of moisture adsorption in a high temperature and high humidity environment and can keep the non-electrostatic adhesion low.
[0076] The binder resin may be a mixture of a low molecular weight resin and a high molecular weight resin. The content ratio of the high molecular weight resin to the low molecular weight resin is preferably 40 / 60 or more and 85 / 15 or less on a mass basis from the viewpoint of low temperature fixability and hot offset resistance.
[0077] <Release agent> Examples of the release agent (wax) used in the toner of the present invention include the following: hydrocarbon waxes such as low molecular weight polyethylene, low molecular weight polypropylene, alkylene copolymers, microcrystalline wax, paraffin wax, and Fischer-Tropsch wax; oxides of hydrocarbon waxes such as oxidized polyethylene wax or block copolymers thereof; waxes containing fatty acid esters as the main component such as carnauba wax; and partially or completely deoxidized fatty acid esters such as deoxidized carnauba wax. Further examples include the following. Saturated straight-chain fatty acids such as palmitic acid, stearic acid, and montanic acid; unsaturated fatty acids such as brassidic acid, eleostearic acid, and valinaric acid; saturated alcohols such as stearyl alcohol, aralkyl alcohol, behenyl alcohol, carnaubyl alcohol, ceryl alcohol, and melissyl alcohol; polyhydric alcohols such as sorbitol; esters of fatty acids such as palmitic acid, stearic acid, behenic acid, and montanic acid with alcohols such as stearyl alcohol, aralkyl alcohol, behenyl alcohol, carnaubyl alcohol, ceryl alcohol, and melissyl alcohol; fatty acid amides such as linoleic acid amide, oleic acid amide, and lauric acid amide; methylene bisstearic acid amide, ethylene biscapric acid amide, ethylene bislauric acid amide, hexamethylene Saturated fatty acid bisamides such as bisstearamide; unsaturated fatty acid amides such as ethylene bisoleamide, hexamethylene bisoleamide, N,N' dioleyl adipamide, and N,N' dioleyl sebacamide; aromatic bisamides such as m-xylene bisstearamide and N,N' distearyl isophthalamide; fatty metal salts (commonly known as metal soaps) such as calcium stearate, calcium laurate, zinc stearate, and magnesium stearate; waxes grafted onto aliphatic hydrocarbon waxes using vinyl monomers such as styrene and acrylic acid; partial esters of fatty acids and polyhydric alcohols such as behenic acid monoglyceride; and methyl ester compounds having hydroxyl groups obtained by hydrogenating vegetable oils and fats.
[0078] Among these waxes, from the viewpoint of improving low-temperature fixing property and fixing separation property, preferred are hydrocarbon waxes such as paraffin wax and Fischer-Tropsch wax, and fatty acid ester waxes such as carnauba wax. In the present invention, the hydrocarbon waxes are more preferred from the viewpoint of further improving hot offset resistance.
[0079] In the present invention, the wax is preferably used in an amount of 3 parts by mass or more and 8 parts by mass or less per 100 parts by mass of the binder resin.
[0080] In addition, in an endothermic curve during temperature rise measured by a differential scanning calorimetry (DSC) device, the peak temperature of the maximum endothermic peak of the wax is preferably 45° C. or more and 140° C. or less. If the peak temperature of the maximum endothermic peak of the wax is within the above range, it is preferable because it is possible to achieve both storage stability and hot offset resistance of the toner.
[0081] <Coloring agent> The toner particles in the present invention may contain a colorant. Examples of the colorant include the following.
[0082] Examples of black colorants include carbon black, yellow colorants, magenta colorants, and cyan colorants used to tone the color to black. Although a pigment may be used alone as the colorant, it is more preferable to use a dye and a pigment in combination to improve the clarity of the colorant from the viewpoint of image quality of a full-color image.
[0083] Magenta toner pigments include the following: CI Pigment Red 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 21, 22, 23, 30, 31, 32, 37, 38, 39, 40, 41, 48:2, 48:3, 48:4, 49, 50, 51, 52, 53, 54, 55, 57:1, 58, 60, 63, 64, 68, 81:1, 83, 87, 88, 89, 90, 112, 114, 122, 123, 146, 147, 150, 163, 184, 202, 206, 207, 209, 238, 269, 282; CI Pigment Violet 19; CI Bat Red 1, 2, 10, 13, 15, 23, 29, 35.
[0084] Dyes for magenta toners include solvent dyes such as CI Solvent Red 1, 3, 8, 23, 24, 25, 27, 30, 49, 81, 82, 83, 84, 100, 109, 121; CI Disperse Red 9; CI Solvent Violet 8, 13, 14, 21, 27; CI Disperse Violet 1; basic dyes such as CI Basic Red 1, 2, 9, 12, 13, 14, 15, 17, 18, 22, 23, 24, 27, 29, 32, 34, 35, 36, 37, 38, 39, 40; and CI Basic Violet 1, 3, 7, 10, 14, 15, 21, 25, 26, 27, 28.
[0085] Pigments for cyan toners include the following: CI Pigment Blue 2, 3, 15:2, 15:3, 15:4, 16, 17; CI Vat Blue 6; CI Acid Blue 45; copper phthalocyanine pigments having 1 to 5 phthalimidomethyl groups substituted on the phthalocyanine skeleton.
[0086] Dyes for cyan toners include CI Solvent Blue 70.
[0087] Yellow toner pigments include: CI Pigment Yellow 1, 2, 3, 4, 5, 6, 7, 10, 11, 12, 13, 14, 15, 16, 17, 23, 62, 65, 73, 74, 83, 93, 94, 95, 97, 109, 110, 111, 120, 127, 128, 129, 147, 151, 154, 155, 168, 174, 175, 176, 180, 181, 185; CI Vat Yellow 1, 3, 20.
[0088] Yellow toner dyes include CI Solvent Yellow 162.
[0089] These colorants can be used alone or in combination, or in the form of a solid solution. The colorant is selected in consideration of hue angle, chroma, brightness, light resistance, transparency on an OHP sheet, and dispersibility in a toner.
[0090] The content of the colorant is preferably 0.1 parts by mass or more and 30.0 parts by mass or less with respect to 100 parts by mass of the total amount of the resin components of the toner.
[0091] <Inorganic fine particles> The toner preferably contains inorganic fine particles for the main purpose of improving fluidity and chargeability, and the inorganic fine particles are preferably attached to the toner surface.
[0092] As inorganic fine particles serving as spacer particles for improving the releasability between the toner and the carrier, silica particles having a maximum peak particle size based on the number distribution of 80 nm to 200 nm are preferred, and in order to function as spacer particles while better suppressing detachment from the toner, a particle size of 100 nm to 150 nm is more preferred.
[0093] In order to improve the fluidity of the toner, it is preferable to contain inorganic fine particles having a maximum peak particle size based on the number distribution of 20 nm to 50 nm, and it is also preferable to use them in combination with the silica particles.
[0094] Further, in order to improve the fluidity and transferability, other external additives may be added to the toner particles. The external additive added to the surface of the toner particles preferably contains inorganic fine particles such as titanium oxide, alumina oxide, and silica, and a plurality of types may be used in combination.
[0095] The total content of the external additives is preferably 0.3 parts by mass to 5.0 parts by mass, more preferably 0.8 parts by mass to 4.0 parts by mass, based on 100 parts by mass of toner particles. Among them, the content of silica particles having a maximum peak particle size of 80 nm to 200 nm based on the number distribution standard is 0.1 parts by mass to 2.5 parts by mass, more preferably 0.5 parts by mass to 2.0 parts by mass. Within this range, the effect as a spacer particle is more remarkable.
[0096] The surfaces of silica particles or inorganic fine particles used as external additives are preferably subjected to a hydrophobic treatment, which is preferably carried out with a coupling agent such as various titanium coupling agents or silane coupling agents, a fatty acid or a metal salt thereof, silicone oil, or a combination thereof.
[0097] Examples of titanium coupling agents include the following: tetrabutyl titanate, tetraoctyl titanate, isopropyl triisostearoyl titanate, isopropyl tridecylbenzenesulfonyl titanate, and bis(dioctyl pyrophosphate)oxyacetate titanate.
[0098] Examples of silane coupling agents include the following: γ-(2-aminoethyl)aminopropyltrimethoxysilane, γ-(2-aminoethyl)aminopropylmethyldimethoxysilane, γ-methacryloxypropyltrimethoxysilane, N-β-(N-vinylbenzylaminoethyl)γ-aminopropyltrimethoxysilane hydrochloride, hexamethyldisilazane, methyltrimethoxysilane, butyltrimethoxysilane, isobutyltrimethoxysilane, hexyltrimethoxysilane, octyltrimethoxysilane, decyltrimethoxysilane, dodecyltrimethoxysilane, phenyltrimethoxysilane, o-methylphenyltrimethoxysilane, and p-methylphenyltrimethoxysilane.
[0099] Examples of fatty acids include long-chain fatty acids such as undecylic acid, lauric acid, tridecylic acid, dodecylic acid, myristic acid, palmitic acid, pentadecylic acid, stearic acid, heptadecylic acid, arachidic acid, montanic acid, oleic acid, linoleic acid, and arachidonic acid. Examples of metals in the fatty acid metal salts include zinc, iron, magnesium, aluminum, calcium, sodium, and lithium.
[0100] Examples of silicone oils include dimethyl silicone oil, methylphenyl silicone oil, and amino-modified silicone oil.
[0101] The hydrophobic treatment is preferably carried out by adding a hydrophobic treatment agent to the particles to be treated in an amount of 1% by mass or more and 30% by mass or less (more preferably 3% by mass or more and 7% by mass or less) relative to the particles to be treated, thereby coating the particles to be treated.
[0102] The degree of hydrophobization of the hydrophobized external additive is not particularly limited, but for example, the hydrophobization degree after the treatment is preferably from 40 to 98. The hydrophobization degree indicates the wettability of a sample with respect to methanol, and is an index of hydrophobicity.
[0103] When the toner is mixed with the magnetic carrier of the present invention to be used as a two-component developer, good results are usually obtained when the carrier mixing ratio is 2% by mass or more and 15% by mass or less, preferably 4% by mass or more and 13% by mass or less, in terms of the toner concentration in the developer. If the toner concentration is less than 2% by mass, the image density is likely to decrease, and if it exceeds 15% by mass, fogging and scattering inside the machine are likely to occur.
[0104] In addition, in a replenishing developer to be replenished to a developing device in response to a decrease in the toner concentration of the two-component developer in the developing device, the amount of toner is 2 parts by mass or more and 50 parts by mass or less per part by mass of the replenishing magnetic carrier.
[0105] <Toner manufacturing method> The method for producing the toner particles is not particularly limited, but a pulverization method is preferred from the viewpoint of dispersion of the release agent and the polymer in which a styrene-acrylic polymer is graft-polymerized to a polyolefin. The procedure for producing the toner by the pulverization method will be described below.
[0106] In the raw material mixing process, materials constituting the toner particles, such as binder resin, release agent, colorant, crystalline polyester, and other components such as charge control agent as necessary, are weighed out in predetermined amounts, blended, and mixed. Examples of mixing devices include double con mixers, V-type mixers, drum mixers, super mixers, Henschel mixers, Nauta mixers, and Mechano Hybrids (manufactured by Nippon Coke & Engineering Co., Ltd.).
[0107] Next, the mixed materials are melt-kneaded to disperse the wax in the binder resin. In the melt-kneading process, a batch-type kneader such as a pressure kneader or a Banbury mixer, or a continuous kneader can be used, and single-screw or twin-screw extruders are mainstream due to their advantage of continuous production. For example, a KTK twin-screw extruder (manufactured by Kobe Steel, Ltd.), a TEM twin-screw extruder (manufactured by Toshiba Machine Co., Ltd.), a PCM kneader (manufactured by Ikegai Iron Works Co., Ltd.), a twin-screw extruder (manufactured by KCK Corporation), a Co-kneader (manufactured by Buss Co., Ltd.), and Kneadex (manufactured by Nippon Coke and Engineering Co., Ltd.) can be mentioned. Furthermore, the resin composition obtained by melt-kneading may be rolled with a two-roller or the like, and cooled with water or the like in a cooling process.
[0108] The cooled resin composition is then pulverized to a desired particle size in a pulverization process, which involves coarse pulverization using a pulverizer such as a crusher, hammer mill, or feather mill, followed by further pulverization using a pulverizer such as a Cryptron System (Kawasaki Heavy Industries), a Super Rotor (Nisshin Engineering), a Turbo Mill (Turbo Kogyo), or an air jet type pulverizer.
[0109] Thereafter, as necessary, the mixture is classified using a classifier or sieve such as an inertial classification type Elbow Jet (manufactured by Nittetsu Mining Co., Ltd.), a centrifugal classification type Turboplex (manufactured by Hosokawa Micron Corporation), a TSP Separator (manufactured by Hosokawa Micron Corporation), or a Faculty (manufactured by Hosokawa Micron Corporation).
[0110] Thereafter, the toner particles are surface-treated by heating to increase the circularity of the toner. For example, the surface treatment can be performed by hot air using a surface treatment device shown in FIG.
[0111] The mixture supplied by the material supply means 31 is introduced into an introduction pipe 33, which is installed vertically to the material supply means, by compressed gas adjusted by compressed gas adjustment means 32. The mixture passing through the introduction pipe is uniformly dispersed by a conical protruding member 34 installed in the center of the material supply means, and is introduced into eight supply pipes 35 that spread radially in eight directions and is subjected to heat treatment. At this time, the flow of the mixture supplied to the treatment chamber is regulated by a regulating means 39 for regulating the flow of the mixture, which is installed in the treatment chamber. Therefore, the mixture supplied to the treatment chamber is heat-treated while swirling in the treatment chamber, and then cooled.
[0112] Hot air for heat-treating the supplied mixture is supplied from hot air supplying means 37, and is introduced into the treatment chamber by spirally swirling the hot air using a swirling member 43 for swirling the hot air. The configuration is such that the swirling member 43 for swirling the hot air has a plurality of blades, and the swirling of the hot air can be controlled by the number and angle of the blades. The hot air supplied into the treatment chamber preferably has a temperature of 100°C to 300°C at the outlet of the hot air supplying means 37. If the temperature at the outlet of the hot air supplying means is within the above range, it is possible to uniformly spheronize the toner particles while preventing the toner particles from fusing or coalescing due to excessive heating of the mixture.
[0113] The heat-treated toner particles are then cooled by cold air supplied from cold air supply means 38, and the temperature of the cold air supplied from cold air supply means 38 is preferably -20°C to 30°C. If the temperature of the cold air is within the above range, the heat-treated toner particles can be efficiently cooled, and the fusion and coalescence of the heat-treated toner particles can be prevented without impeding the uniform spheroidization of the mixture. The absolute moisture content of the cold air is 0.5 g / m 3 More than 15.0g / m 3 It is preferable that:
[0114] Next, the cooled heat-treated toner particles are collected by the collecting means 40 at the bottom end of the processing chamber. A blower (not shown) is provided ahead of the collecting means, so that the toner particles are sucked and transported by the blower.
[0115] The powder particle supply port 44 is provided so that the swirling direction of the supplied mixture and the swirling direction of the hot air are the same, and the recovery means 40 of the surface treatment device is provided on the outer periphery of the treatment chamber so as to maintain the swirling direction of the swirled powder particles. Furthermore, the cold air supplied from the cold air supply means 38 is configured to be supplied from the outer periphery of the device to the circumferential surface inside the treatment chamber in a horizontal and tangential direction. The swirling direction of the toner supplied from the powder supply port, the swirling direction of the cold air supplied from the cold air supply means, and the swirling direction of the hot air supplied from the hot air supply means are all the same. Therefore, no turbulence occurs in the treatment chamber, the swirling flow in the device is strengthened, a strong centrifugal force is applied to the toner, and the dispersibility of the toner is further improved, so that a toner with a uniform shape and few coalesced particles can be obtained.
[0116] When the average circularity of the toner is 0.960 or more and 0.980 or less, the non-electrostatic adhesion can be kept low, which is preferable from the viewpoint of suppressing fogging.
[0117] Next, a method for measuring the average particle size of the toner will be described below.
[0118] <Method of measuring weight average particle diameter (D4) and number average particle diameter (D1) of toner> The weight-average particle size (D4) and number-average particle size (D1) of the toner were measured using a precision particle size distribution measuring device using the narrow hole electrical resistance method, "Coulter Counter Multisizer 3" (registered trademark, manufactured by Beckman Coulter, Inc.), equipped with a 100 μm aperture tube, and the accompanying dedicated software "Beckman Coulter Multisizer 3 Version 3.51" (manufactured by Beckman Coulter, Inc.), for setting measurement conditions and analyzing measurement data. Measurements were made with an effective measurement channel count of 25,000 channels, and the measurement data was analyzed and calculated.
[0119] The electrolyte solution used for the measurement is prepared by dissolving special grade sodium chloride in ion-exchanged water to a concentration of approximately 1% by mass, for example, "ISOTON II" (manufactured by Beckman Coulter).
[0120] Before performing the measurements and analysis, the dedicated software was set up as follows.
[0121] In the "Change Standard Measurement Method (SOM) screen" of the dedicated software, set the total count number in the control mode to 50,000 particles, the number of measurements to 1, and the Kd value to the value obtained using "Standard Particle 10.0 μm" (Beckman Coulter). Press the threshold / noise level measurement button to automatically set the threshold and noise level. In addition, set the current to 1600 μA, the gain to 2, the electrolyte to ISOTON II, and check the aperture tube flush after measurement.
[0122] In the "Pulse to particle size conversion setting screen" of the dedicated software, set the bin interval to logarithmic particle size, the particle size bin to 256 particle size bins, and the particle size range from 2 μm to 60 μm.
[0123] The specific measurement method is as follows. (1) Pour about 200 ml of the electrolyte solution into a 250 ml round-bottom glass beaker made exclusively for the Multisizer 3, set it on the sample stand, and stir the stirrer rod counterclockwise at 24 revolutions per second. Then, use the "aperture flush" function of the analysis software to remove dirt and air bubbles from inside the aperture tube. (2) About 30 ml of the electrolyte solution is placed in a 100 ml flat-bottom glass beaker. Add to the beaker a 10% by weight aqueous solution of "Contaminon N" (a pH 7 neutral detergent for cleaning precision measuring instruments, made of a nonionic surfactant, an anionic surfactant, and an organic builder, manufactured by Wako Pure Chemical Industries, Ltd.) as a dispersant. Add approximately 0.3 ml of a solution prepared by diluting 100% ethanol (manufactured by Epson) three times with ion-exchanged water. (3) A specified amount of ion-exchanged water is placed in the water tank of an ultrasonic disperser "Ultrasonic Dispension System Tetora150" (manufactured by Nikkaki Bios Co., Ltd.) that has two built-in oscillators with an oscillation frequency of 50 kHz and a phase shift of 180 degrees and an electrical output of 120 W. About 2 ml of the above-mentioned Conaminon N is added to this water tank. (4) The beaker (2) is set in the beaker fixing hole of the ultrasonic disperser, and the ultrasonic disperser is operated. Then, the height position of the beaker is adjusted so that the resonance state of the liquid surface of the electrolyte solution in the beaker is maximized. (5) While the electrolyte solution in the beaker in (4) is irradiated with ultrasonic waves, about 10 mg of toner is added little by little to the electrolyte solution and dispersed. Then, ultrasonic dispersion treatment is continued for another 60 seconds. During ultrasonic dispersion, the water temperature in the water tank is appropriately adjusted to be 10°C or higher and 40°C or lower. (6) Using a pipette, add the electrolyte solution (5) in which the toner is dispersed to the round-bottom beaker (1) placed in the sample stand, and adjust the measurement concentration to about 5%. Then, measurements are continued until the number of particles measured reaches 50,000. (7) The measurement data is analyzed using the dedicated software that comes with the device, and the weight average particle size (D4) and number average particle size (D1) are calculated. Note that when the dedicated software is set to graph / volume %, the "average diameter" on the analysis / volume statistics (arithmetic mean) screen is the weight average particle size (D4), and when the dedicated software is set to graph / number %, the "average diameter" on the analysis / number statistics (arithmetic mean) screen is the number average particle size (D1).
[0124] [Image forming device / image forming method] Next, an image forming apparatus and an image forming method equipped with a developing device using the magnetic carrier, two-component developer and replenishment developer of the present invention will be described with examples, but the developing device to which the present invention can be suitably applied is not limited to this.
[0125] In FIG. 1, the electrostatic latent image carrier 1 rotates in the direction of the arrow in the figure. The electrostatic latent image carrier 1 is charged by a charger 2, which is a charging means, and the surface of the charged electrostatic latent image carrier 1 is exposed by an exposure device 3, which is an electrostatic latent image forming means, to form an electrostatic latent image. The developing device 4 has a developing container 5 that contains a two-component developer, and the developer carrier 6 is arranged in a rotatable state, and a magnet 7 is contained inside the developer carrier 6 as a magnetic field generating means. At least one of the magnets 7 is installed so as to be in a position facing the latent image carrier. The two-component developer is held on the developer carrier 6 by the magnetic field of the magnet 7, and the amount of the two-component developer is regulated by a regulating member 8, and the developer is transported to a developing section facing the electrostatic latent image carrier 1. In the developing section, a magnetic brush is formed by the magnetic field generated by the magnet 7. Thereafter, a developing bias consisting of an alternating electric field superimposed on a direct current electric field is applied, and the electrostatic latent image is visualized as a toner image. The toner image formed on the electrostatic latent image carrier 1 is electrostatically transferred to a recording medium (transfer material) 12 by a transfer charger 11. Here, as shown in FIG. 2, the image may be once transferred from the electrostatic latent image carrier 1 to an intermediate transfer body 9, and then electrostatically transferred to the recording medium 12.
[0126] Thereafter, the recording medium 12 is conveyed to a fixing device 13, where the toner is fixed onto the recording medium 12 by applying heat and pressure. Thereafter, the recording medium 12 is discharged outside the apparatus as an output image. After the transfer process, the toner remaining on the electrostatic latent image carrier 1 is removed by a cleaner 15. Thereafter, the electrostatic latent image carrier 1 cleaned by the cleaner 15 is electrically initialized by light irradiation from a pre-exposure device 16, and the above image forming operation is repeated.
[0127] FIG. 2 is a schematic diagram showing an example of a full-color image forming apparatus to which the present invention can be applied.
[0128] The arrangement of the image forming units such as K, Y, C, and M in the figure, and the arrows indicating the rotation direction are not limited to those shown. Incidentally, K means black, Y means yellow, C means cyan, and M means magenta. In FIG. 2, the electrostatic latent image carriers 1K, 1Y, 1C, and 1M rotate in the direction of the arrows in the figure. Each electrostatic latent image carrier is charged by the chargers 2K, 2Y, 2C, and 2M, which are charging means, and the surface of each charged electrostatic latent image carrier is exposed by the exposure devices 3K, 3Y, 3C, and 3M, which are electrostatic latent image forming means, to form an electrostatic latent image. After that, the electrostatic latent image is visualized as a toner image by the two-component developer carried on the developer carriers 6K, 6Y, 6C, and 6M provided in the development devices 4K, 4Y, 4C, and 4M, which are development means. Furthermore, it is transferred to the intermediate transfer body 9 by the intermediate transfer chargers 10K, 10Y, 10C, and 10M, which are transfer means. The image is then transferred to a recording medium 12 by a transfer charger 11, which is a transfer means, and the recording medium 12 is heated and pressure fixed by a fixing device 13, which is a fixing means, and output as an image. An intermediate transfer body cleaner 14, which is a cleaning member for the intermediate transfer body 9, collects the toner remaining after transfer. Specifically, the development method of the present invention is preferably performed in a state where an AC voltage is applied to the developer carrier to form an alternating electric field in the development area while the magnetic brush is in contact with the photosensitive body. The distance (SD distance) between the developer carrier (developing sleeve) 6 and the photosensitive drum is 100 μm or more and 1000 μm or less, which is good for preventing carrier adhesion and improving dot reproducibility. If it is narrower than 100 μm, the supply of the developer is likely to be insufficient, and the image density is low. If it exceeds 1000 μm, the magnetic field lines from the magnetic pole S1 spread, the density of the magnetic brush is low, and the dot reproducibility is deteriorated, and the force binding the magnetic coated carrier is weakened, making it easy for carrier adhesion to occur.
[0129] The peak-to-peak voltage (Vpp) of the alternating electric field is 300V or more and 3000V or less, preferably 500V or more and 1800V or less. The frequency is 500Hz or more and 10000Hz or less, preferably 1000Hz or more and 7000Hz or less, and each can be appropriately selected and used depending on the process. In this case, the waveform of the AC bias for forming the alternating electric field can be a triangular wave, a rectangular wave, a sine wave, or a waveform with a changed duty ratio. In order to respond to changes in the toner image formation speed, it is preferable to apply a development bias voltage (intermittent AC superimposed voltage) having a discontinuous AC bias voltage to the developer carrier to perform development. If the applied voltage is lower than 300V, it is difficult to obtain a sufficient image density, and the fog toner in the non-image area may not be well collected. If it exceeds 3000V, the latent image may be disturbed through the magnetic brush, resulting in a decrease in image quality.
[0130] By using a two-component developer having a well-charged toner, the fog removal voltage (Vback) can be lowered, and the primary charge of the photoconductor can be lowered, thereby extending the life of the photoconductor. Although Vback depends on the development system, it is recommended that it be 200V or less, more preferably 150V or less. The contrast potential is preferably 100V or more and 400V or less to obtain sufficient image density.
[0131] In addition, if the frequency is lower than 500 Hz, the process speed is also affected, but the configuration of the electrostatic latent image bearing photoreceptor may be the same as that of a photoreceptor generally used in an image forming apparatus. For example, a photoreceptor having a configuration in which a conductive layer, an undercoat layer, a charge generating layer, a charge transport layer, and, if necessary, a charge injection layer are provided in this order on a conductive substrate such as aluminum or SUS.
[0132] The conductive layer, undercoat layer, charge generating layer and charge transport layer may be layers that are generally used in photoconductors. As the outermost layer of the photoconductor, for example, a charge injection layer or a protective layer may be used.
[0133] [Configuration included in the embodiment of the present invention] The disclosure of this embodiment includes the following configuration. (Configuration 1) A magnetic carrier having a magnetic core particle and a resin coating layer coating the surface of the magnetic core particle, The resin coating layer contains fine particles, The magnetic carrier is characterized in that the fine particles have a fine particle matrix and a structure represented by the above formula (1) present on the surface of the fine particle matrix. (Configuration 2) The magnetic carrier according to configuration 1, wherein the ratio of N element derived from the surface treatment of the fine particles is 0.7 atom % or less when the surface of the magnetic carrier is measured by X-ray photoelectron spectroscopy (XPS). (Configuration 3) The magnetic carrier according to configuration 1 or 2, wherein the coating resin of the resin coating layer is any one of vinyl resins, polyester resins, epoxy resins, and urethane resins. (Configuration 4) The magnetic carrier according to any one of configurations 1 to 3, wherein the fine particle matrix of the fine particles is fine particles of any one of silica, titania, and polymethyl methacrylate resin. (Configuration 5) The magnetic carrier according to any one of Configurations 1 to 4, wherein the number average particle size of the primary particles of the fine particles is 8 nm or more and 100 nm or less. (Configuration 6) The magnetic carrier according to any one of configurations 1 to 5, wherein the resin coating layer has an average thickness of 100 nm or more and 1000 nm or less. (Configuration 7) The magnetic carrier according to any one of configurations 1 to 6, wherein the amount of the fine particles added is from 1 part by mass to 100 parts by mass when the coating resin of the resin coating layer is taken as 100 parts by mass. (Configuration 8) The magnetic carrier according to any one of configurations 1 to 7, wherein the surface of the microparticle matrix has a structure represented by the above formula (3-1) or (3-2). (Configuration 9) A two-component developer comprising the magnetic carrier according to any one of Configurations 1 to 8 and a toner. EXAMPLES
[0134] <Surface-treated particles> 100 parts by mass of base particles of the fine particles shown in Table 1 were treated with a treating agent having a structure shown in Table 2 in the amount shown, to produce surface-treated fine particles 1 to 19.
[0135] [Table 1]
[0136] [Table 2-1]
[0137] [Table 2-2]
[0138] <Production Example of Magnetic Carrier Core 1 (Porous Magnetic Core Particles)> Step 1 (weighing and mixing step): Fe2O368.1% by mass MnCO328.6% by mass Mg(OH)21.9% by mass SrCO31.4% by mass The ferrite raw material was weighed, and 80 parts by mass of the ferrite raw material was mixed with 20 parts by mass of water and pulverized to prepare a slurry having a solid content of 80% by mass.
[0139] Step 2 (pre-firing step): The resulting slurry was dried using a spray dryer (manufactured by Okawara Kakoki Co., Ltd.) and then fired in a batch-type electric furnace in a nitrogen atmosphere (oxygen concentration 1.0% by volume) at a temperature of 1040° C. for 3.0 hours to produce calcined ferrite.
[0140] Step 3 (Crushing step): The obtained calcined ferrite was crushed to about 0.5 mm with a crusher, and water was added to prepare a slurry. The solid content of the slurry was set to 70 mass %. The slurry was crushed for 3 hours with a wet ball mill using stainless steel beads with a diameter of 1 / 8 inch, and further crushed for 4 hours with a wet bead mill using zirconia with a diameter of 1 mm, to obtain a calcined ferrite slurry with a volume-based 50% particle size (D50) of 1.2 μm.
[0141] Process 4 (granulation process): To the calcined ferrite slurry, 1.0 part by mass of ammonium polycarboxylate as a dispersant and 1.5 parts by mass of polyvinyl alcohol as a binder were added per 100 parts by mass of the calcined ferrite, and the mixture was granulated into spherical particles using a spray dryer (manufactured by Okawara Kakoki Co., Ltd.) and dried. The resulting granulated material was subjected to particle size adjustment, and then heated at 730°C for 2 hours using a rotary electric furnace to remove organic substances such as the dispersant and binder.
[0142] Step 5 (firing): In a nitrogen atmosphere (oxygen concentration 1.0% by volume), the time from room temperature to the firing temperature (1150°C) was set to 2 hours, and the temperature was held at 1100°C for 4 hours for firing. After that, the temperature was lowered to 60°C over 8 hours, and the material was returned from the nitrogen atmosphere to the air and taken out at a temperature of 40°C or less.
[0143] Step 6 (sorting step): After the aggregated particles were crushed, the particles were sieved through a sieve with 150 μm openings to remove coarse particles, air classification was carried out to remove fine powder, and further magnetic separation was carried out to remove low magnetic force particles to obtain ferrite-based core material particles. The obtained ferrite-based core material particles were porous and had pores.
[0144] Process 7 (filling process): 100 parts by mass of the obtained ferrite-based core particles were placed in the stirring vessel of a mixer (Dalton's universal stirrer NDMV type), and nitrogen was introduced while maintaining the temperature at 60°C and reducing the pressure to 2.3 kPa. 50 parts by mass of methylphenyl silicone resin and 50 parts by mass of toluene were mixed for 10 minutes with a multi-blender mixer, and then dropped onto the ferrite-based core particles. The amount of dripping was adjusted so that the solid content of the resin component was 5.1 parts by mass per 100 parts by mass of the ferrite-based core particles.
[0145] After the dropwise addition was completed, stirring was continued for 2.5 hours, the temperature was then raised to 70° C., the solvent was removed under reduced pressure, and the inside of the ferrite-based core particles was filled with the above-mentioned resin composition.
[0146] After cooling, the obtained ferrite-based core material particles were transferred to a mixer (a UD-AT type drum mixer manufactured by Sugiyama Heavy Industries Co., Ltd.) with a spiral blade in a rotatable mixing container, and the temperature was raised to a set temperature of 220°C at a heating rate of 2°C / min under a nitrogen atmosphere. Heating and stirring were carried out at this temperature for 1.0 hour to harden the resin, and stirring was continued for an additional 1.0 hour while maintaining the temperature at 200°C.
[0147] After that, it was cooled to room temperature, and the ferrite-based core particles filled with resin and hardened were taken out, and non-magnetic materials were removed using a magnetic separator. Furthermore, coarse particles were removed using a vibrating sieve to obtain magnetic carrier cores 1 filled with resin. The 50% particle size (D50) based on volume distribution of magnetic carrier cores 1 was 40.1 μm. The physical properties of the obtained magnetic carrier cores 1 are shown in Table 3.
[0148] <Magnetic carrier core 2 (production example of ferrite core particles)> Process 1 (weighing and mixing process): Fe2O361.4% by mass MnCO334.4% by mass Mg(OH)23.1% by mass SrCO31.1% by mass The ferrite raw materials were weighed so that the weight of the mixture was 100g / g, and then crushed and mixed for 2 hours in a dry ball mill using zirconia balls (φ10 mm).
[0149] Step 2 (pre-firing step): After crushing and mixing, the mixture was sintered in air at 950°C for 2 hours in a burner-type sintering furnace to produce calcined ferrite.
[0150] Step 3 (Crushing step): After crushing to about 0.5 mm with a crusher, 30 parts by mass of water was added to 100 parts by mass of the calcined ferrite and crushed in a wet ball mill using stainless steel balls (φ1.0 mm) for 2 hours. After separating the balls, the mixture was crushed in a wet bead mill using stainless steel balls (φ1.0 mm) for 3 hours to obtain a ferrite slurry.
[0151] Process 4 (granulation process): To the ferrite slurry, 1.5 parts by mass of polyvinyl alcohol was added as a binder per 100 parts by mass of the calcined ferrite, and the mixture was granulated using a spray dryer (manufacturer: Okawara Kakoki).
[0152] Step 5 (final firing): In order to control the firing atmosphere, firing was performed in an electric furnace under a nitrogen atmosphere (oxygen concentration: 0.6% by volume) at 1250° C. for 6 hours.
[0153] Step 6 (sorting step): The aggregated particles were disintegrated, and then sieved through a sieve with 250 μm openings to remove coarse particles, thereby obtaining magnetic carrier cores 2 having a D50 of 35.1 μm. The physical properties of the obtained magnetic carrier cores 2 are shown in Table 3.
[0154] <Preparation of magnetic particles A> While passing nitrogen gas at 20 L / min through a reaction vessel equipped with a gas inlet tube, Fe 2+ 26.7L of ferrous sulfate solution containing 1.5 mol / L and Si 4+ 1.0L of 0.2 mol / L sodium silicate No. 3 aqueous solution was added to 22.3L of 3.4 mol / L sodium hydroxide aqueous solution, the pH was adjusted to 6.8, and the temperature was raised to 90°C. 1.2L of 3.5 mol / L sodium hydroxide aqueous solution was added to adjust the pH to 8.5, stirring was continued, and the gas was replaced with air and aerated at 100L / min for 90 minutes. The pH was neutralized to 7 using dilute sulfuric acid, and the resulting particles were washed with water, filtered, dried, and pulverized to obtain magnetic particles A with a number average particle size of 0.30μm.
[0155] The magnetic particles A thus obtained and a silane coupling agent (3-glycidoxypropylmethyldimethoxysilane; 1.2 parts by mass per 100 parts by mass of the magnetite fine particles) were introduced into a vessel, and the mixture was mixed and stirred at high speed at 100° C. for 1 hour in the vessel to perform a surface treatment of the magnetic particles A.
[0156] <Preparation of magnetic particles B> Similar to the magnetic particles A, 100 parts by mass of spherical hematite particles having a number-average particle size of 0.40 μm were subjected to surface treatment with 1.2 parts by mass of a silane coupling agent (3-(2-aminoethylamino)propyltrimethoxysilane).
[0157] <Production Example of Magnetic Carrier Core 3 (Magnetic Material Dispersed Resin Core Particles)> Phenol 10.0 parts by mass Formaldehyde solution (37% by weight formaldehyde aqueous solution) 15.0 parts by weight Surface-treated magnetic particles A 95.0 parts by mass Surface-treated magnetic particles B 5.0 parts by mass 25% ammonia water 3.5 parts by weight Water 15.0 parts by mass The above materials were introduced into a reactor, heated to 40°C, and mixed thoroughly. Then, the materials were heated to 85°C at an average heating rate of 1.5°C / min while stirring, and held at 85°C for 3 hours to polymerize and harden. The peripheral speed of the stirring blades was 1.96 m / sec.
[0158] After the polymerization reaction, the mixture was cooled to 30°C and water was added. The supernatant was removed to obtain a precipitate, which was washed with water and then air-dried. The air-dried product was dried at 180°C for 5 hours under reduced pressure (5 mmHg or less) to obtain magnetic carrier cores 3, which are magnetic material-dispersed resin particles. The physical properties of the obtained magnetic carrier cores 3 are shown in Table 1.
[0159] [Table 3]
[0160] <Production Examples of Magnetic Carriers 1 to 19> The coating resin shown in Table 4 and the fine particles shown in Table 5 were combined in the amount shown in Table 5 per 100 parts by mass of the resin solid content of the coating resin, and 200 parts by mass of toluene was further added and stirred. The stirred coating solution and the magnetic carrier cores shown in Table 3 were then put into a vacuum degassing kneader. The amount of the coating solution was adjusted so that the coating film thickness of the magnetic carrier was as shown in Table 5.
[0161] Mixing was continued at room temperature for 15 minutes at 30 rpm, and then the temperature was raised to 100° C. and the pressure was reduced to 0.10 MPa, and mixing was continued at 30 rpm for 30 minutes to remove the solvent and perform a coating operation.
[0162] Thereafter, the magnetic carrier coated with the solid components of the coating liquid was transferred to a mixer (a UD-AT type drum mixer manufactured by Sugiyama Heavy Industries Co., Ltd.) having a spiral blade in a rotatable mixing container. The mixture was heat-treated at 120°C for 2 hours in a nitrogen atmosphere while stirring at 10 revolutions per minute. The magnetic carrier 1 thus obtained was separated into low magnetic products by magnetic separation, passed through a sieve with an opening of 150 μm, and then classified by an air classifier to obtain the magnetic carrier 1.
[0163] In the same manner as in the preparation of the above magnetic carrier 1, magnetic carriers 2 to 19 were obtained using the carrier core type shown in Table 3 above, the coating resin type shown in Table 4 above, and the combination shown in Table 5 above.
[0164] [Table 4]
[0165] [Table 5]
[0166] <Toner 1 Manufacturing Example> Polyester resin 95 parts by weight [·Bisphenol A ethylene oxide (2.2 mole adduct) 50.0 mole parts Bisphenol A propylene oxide (2.2 mole adduct) 50.0 mole parts Terephthalic acid: 90.0 parts by mole Trimellitic anhydride: 10.0 mol parts Crystalline polyester 15 parts by weight [·1,10-decanedicarboxylic acid 50.0 mol parts Ethylene glycol 50.0 mol parts Fischer-Tropsch wax (maximum endothermic peak temperature 90°C) 3.5 parts by mass CI Pigment Blue 15:3 4.5 parts by weight The above materials were mixed using a Henschel mixer (FM-75, manufactured by Mitsui Mining Co., Ltd.) at a rotation speed of 1500 rpm for a rotation time of 5 min, and then kneaded using a twin-screw kneader (PCM-30, manufactured by Ikegai Co., Ltd.) set at a temperature of 130°C. The kneaded material obtained was cooled and coarsely crushed to 1 mm or less using a hammer mill to obtain a coarsely crushed material. The coarsely crushed material obtained was finely crushed using a mechanical crusher (T-250, manufactured by Turbo Kogyo Co., Ltd.). Further, classification was performed using a Faculty (F-300, manufactured by Hosokawa Micron Corporation) to obtain toner base particles 1 having a weight average particle diameter of 5.5 μm.
[0167] Toner base particles 1 100 parts by weight Silica fine particles A (number average particle size (D1) is 120 nm) 2.0 parts by mass The raw materials shown in the above recipe were mixed using a Henschel mixer (FM-10C type, manufactured by Mitsui Mining Co., Ltd.) at a rotation speed of 1900 rpm for a rotation time of 3 minutes, and then heat-treated using the surface treatment device shown in Figure 3 to obtain heat-treated toner particles 1. The operating conditions were feed rate = 5 kg / hr, hot air temperature = 160°C, and hot air flow rate = 6 m 3 / min., cold air temperature = -5℃, cold air flow rate = 4m 3 / min., Blower air volume = 20m 3 / min., Injection air flow rate = 1m 3 / min.
[0168] Heat-treated toner particles 1 100 parts by weight Silica fine particles B (number average particle size (D1) is 20 nm) 0.6 parts by mass The above materials were mixed in a Henschel mixer (FM-75, manufactured by Mitsui Miike Chemical Engineering Co., Ltd.) at a rotation speed of 1900 rpm for a rotation time of 3 minutes to obtain Toner 1 (weight average particle diameter 5.6 μm).
[0169] Example 1 8.0 parts by mass of toner 1 was added to 91 parts by mass of magnetic carrier 1, and the mixture was shaken with a shaker (YS-8D type: manufactured by Yayoi Co., Ltd.) to prepare 330 g of two-component developer 1. The vibration conditions of the shaker were 150 rpm and 2 minutes.
[0170] On the other hand, 90 parts by mass of toner 1 was added to 10 parts by mass of magnetic carrier 1, and mixed for 5 minutes in a V-type mixer in an environment of normal temperature and humidity of 23° C. / 50% RH to obtain refill developer 1.
[0171] The two-component developer 1 and the replenishing developer 1 were used for the following evaluation.
[0172] A modified imagePRESS V1000 (Canon) was used as the image forming apparatus, and two-component developer 1 was placed in the developer unit at the cyan position, and a replenishment developer container containing replenishment developer 1 was set. The modifications were made so that the DC voltage VDC of the developer carrier, the charging voltage VD of the electrostatic latent image carrier, the laser power, and the total discharge current of the charger could be freely set.
[0173] For the image output evaluation, an FFH image (solid image) with the desired image ratio was output, and the VDC, VD, and laser power were adjusted so that the toner loading amount of the FFH image was the desired amount, and the evaluation described below was performed. FFH is a value that expresses 256 gradations in hexadecimal, with 00H being the first gradation (white background) of the 256 gradations and FFH being the 256th gradation (solid area) of the 256 gradations. The evaluation was also performed using CS-680 (68.0 g / m 2 ) (sold by Canon Marketing Japan Inc.) was used.
[0174] [Rating X: Image density stability when changing from a high humidity environment to a low humidity environment] In a high humidity environment of 30℃ and 80%RH (hereinafter referred to as H / H environment), 10,000 charts with 30% image area ratio FFH output were printed per day, for a total of 300,000 sheets printed over 30 days. After that, eight band images were printed with each pattern set to the density shown below. Image density was measured using a spectrodensitometer 500 series (manufactured by X-Rite). Pattern 1: 0.10~0.14 Pattern 2: 0.25~0.29 Pattern 3: 0.45~0.49 Pattern 4: 0.65~0.69 Pattern 5: 0.85~0.89 Pattern 6: 1.05~1.09 Pattern 7: 1.25~1.29 Pattern 8: 1.48~1.52
[0175] After the above image output, the image forming device was left to stand for one day in the H / H environment, and then moved to a room with a temperature of 23°C and a humidity of 5% RH (hereinafter referred to as the N / L environment), where the image forming device was immediately turned on so that it could output an image. Immediately after the image forming device started up and was able to output an image, the above eight band images were output. After that, the above eight band images were output every minute, and the time required for all eight patterns of density ranges to be complete for the image output in the H / H environment was evaluated. The evaluation is as follows. The results are shown in Table 6. A (10 points): 3 minutes or less B (9 points): 4 minutes C (8 points): 5 minutes D (7 points): 6 minutes E (6 points): 7 minutes F (5 points): 8 minutes G (4 points): 9 minutes H (3 points): 10 minutes I (2 points): 11 minutes or more For the X rating, a score of 7 or above was considered a passing grade.
[0176] [Evaluation Y: Concentration stability in low humidity environment] In the N / L environment, a FFH image of 50 mm x 50 mm in size was printed in the center of the paper. The development contrast at which the image density became 1.60 was defined as Vi (V).
[0177] Next, a chart with an image area ratio of 2% FFH output was output 5,000 sheets per day in an N / L environment. Immediately after outputting 5,000 sheets, an FFH image with a size of 50 mm x 50 mm was output in the center of the paper in the same environment, and the development contrast at which the image density became 1.58 to 1.62 was defined as Vf (V).
[0178] The density stability in a low humidity environment was evaluated as the difference in development contrast (Vi-Vf(V)). The results are shown in Table 6. A (10 points): Less than 50V B (9 points): 50V or more and less than 55V C (8 points): 55V or more and less than 60V D (7 points): 60V or more and less than 65V E (6 points): 65V or more and less than 70V F (5 points): 70V or more and less than 75V G (4 points): 75V or more and less than 80V H (3 points): 80V or more and less than 85V I (2 points): 85V or more For evaluation Y, a score of 7 or above was considered a passing grade.
[0179] [Evaluation Z: Difference in development contrast when outputting a solid image in a low humidity environment and a high humidity environment] In the N / L environment, 1000 sheets of a chart with an image area ratio of 2% FFH output were printed. Then, in the same environment, a 50mm x 50mm FFH image was printed in the center of the paper. The development contrast at which the image density became 1.58 to 1.62 was defined as VL (V).
[0180] Next, 1000 sheets of a chart with an image area ratio of 30% FFH output were printed in an H / H environment. After that, an FFH image with a size of 50 mm x 50 mm was printed in the center of the paper in the same environment. The development contrast at which the image density became 1.58 to 1.62 was defined as VH (V).
[0181] The evaluation of the difference in development contrast when outputting a solid image in a low humidity environment and a high humidity environment was made as (VL-VH(V)). The results are shown in Table 6. A (10 points): Less than 100V B (9 points): 100V or more and less than 110V C (8 points): 110V or more and less than 120V D (7 points): 120V or more and less than 130V E (6 points): 130V or more and less than 140V F (5 points): 140V or more and less than 150V G (4 points): 150V or more and less than 160V H (3 points): 160V or more and less than 170V I (2 points): 170V or more For the Z rating, a score of 7 or above was considered a passing grade.
[0182] [Total score] Table 6 also shows the total scores for each evaluation, with a total score of 20 or above being considered a pass.
[0183] [Examples 2 to 15, Comparative Examples 1 to 4] Except for changing the magnetic carrier 1 to the magnetic carrier shown in Table 6, two-component developers and replenishment developers according to Examples 2 to 15 and Comparative Examples 1 to 4 were prepared using each combination of magnetic carrier and toner 1 in the same manner as in Example 1, and were evaluated in the same manner as in Example 1. The evaluation results are shown in Table 6.
[0184] [Table 6]
Claims
1. A magnetic carrier having a magnetic core particle and a resin coating layer coating the surface of the magnetic core particle, The resin coating layer contains fine particles, The magnetic carrier is characterized in that the fine particles have a fine particle matrix and a structure represented by the following formula (1) present on the surface of the fine particle matrix. *-X 1 -Formula A (1) [X 1 satisfies the following provision (i) or (ii): (i) -(SiR a R b —O)n-, R a and R b is CH 3 Or C 6 H 5 and R a and R b may be the same or different, and n is an integer of 3 to 20. (ii) -(CH 2 -CR c R d ) m-, R c and R d is H, CH 3 , C 2 H 5 Or C 3 H 7 R c and R d may be the same or different, and m is an integer of 2 or more and 10 or less; A is, X 1 When the compound has the structure of (i), it is a structure represented by the following formula (2-1) or the following formula (2-2): X 1 When the compound has the structure (ii), the compound is any structure selected from the group consisting of the following formulas (2-3) to (2-5): * indicates a bonding portion with the microparticle matrix. 【Chemistry 1】 (R in the above formulas (2-1) to (2-5) e and R f is H, CH 3 , C 2 H 5 , C 3 H 7 , C 4 H 9 , C 6 H 5 , C.H. 2 O.H., C. 2 H 4 OH or CH 2 O-CH 3 R e and R f may be the same or different. R g and R h is CH 3 , O-CH 3 Or O-C 2 H 5 R g and R h may be the same or different. R i is H or CH 3 It is. p, q, and r each represent an integer of 1 or more and 10 or less; s and t each represent an integer of 1 or more and 10 or less; Each of u, v, and w represents an integer of 1 or more and 10 or less.
2. 2. The magnetic carrier according to claim 1, wherein the coating resin of the resin coating layer is any one of vinyl resins, polyester resins, epoxy resins, and urethane resins.
3. 3. The magnetic carrier according to claim 1, wherein the fine particle matrix of the fine particles is fine particles of any one of silica, titania, and polymethyl methacrylate resin.
4. 3. The magnetic carrier according to claim 1, wherein the number average particle size of the primary particles of the fine particles is 8 nm or more and 100 nm or less.
5. 3. The magnetic carrier according to claim 1, wherein the resin coating layer has an average thickness of 100 nm or more and 1000 nm or less.
6. 3. The magnetic carrier according to claim 1, wherein the amount of the fine particles added is 1 part by mass or more and 100 parts by mass or less when the coating resin of the resin coating layer is taken as 100 parts by mass.
7. 3. The magnetic carrier according to claim 1, wherein the surface of the microparticle matrix has a structure represented by the following formula (3-1) or (3-2): 【Chemistry 2】 (R in the above formula (3-1) or (3-2) a and R b is CH 3 Or C 6 H 5 and R a and R b may be the same or different, R e and R f is H, CH 3 , C 2 H 5 , C 3 H 7 , C 4 H 9 , C 6 H 5 , C.H. 2 O.H., C. 2 H 4 OH or CH 2 O-CH 3 R e and R f may be the same or different. R g and R h is CH 3 , O-CH 3 Or O-C 2 H 5 R g and R h may be the same or different. n is 3 or more and 20 or less, and p, q, and r are integers of 1 or more and 10 or less.
8. A two-component developer comprising the magnetic carrier according to claim 1 or 2 and a toner.
Citation Information
Patent Citations
JP1974066880A
JP1975079563A
Evaluating device for adhesive strength of magnetic tape
JP1989003816A
Organosiloxane compound whose one terminus is terminated with aminoalkyl
JP1989193276A
Electrostatic latent image developing carrier
JP2001051456A